(untitled) - Birnbaum, Z. W. (New York, 1962)
INTRODUCTION TO PROBABILITY AND MATHEMATICAL STATISTICS focuses on developing the skills to build probability (stochastic) models. The mathematical development of the subject, with examples and exercises oriented toward applications.
Keywords: Mathematical statistics,Toán thống kê